ANALISIS YURIDIS PERTIMBANGAN DAN KONSEKUENSI TERHADAP PENOLAKAN ITSBAT DALAM PUTUSAN NOMOR 124/PDT.G/2023/MS.BNA - Nurjannah, Via; Rizkal (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This research employs a normative juridical method. Primary legal materials used include the Marriage Law and Decision Number 124/Pdt.G/2023/MS.Bna. Data analysis is conducted systematically based on library research, involving primary, secondary, and tertiary legal sources. The results of the study show that the judges' consideration in rejecting the isbat nikah petition in Decision Number 124/Pdt.G/2023/MS. Bna was based on the fact that the first petitioner was still legally married to another woman, with the marriage duly registered at the Office of Religious Affairs (KUA). Juridically, the rejection is valid and in accordance with the prevailing legal provisions, particularly referring to Supreme Court Circular (SEMA) Number 3 of 2018, which states that isbat nikah petitions for polygamous marriages based on unregistered (sirri) marriages must be declared inadmissible.